BIMBINGAN BELAJAR BAHASA INGGRIS BAGI SISWA SEKOLAH DASAR DI DESA PRINGGARATA KECAMATAN PRINGGARATA - Danul Aristiawan; Herman (Universitas Majalengka, 2023)
The Community Service Program that has been carried out is an English tutoring program for elementary school students in Pringgarata Village, Pringgarata District, Central Lombok Regency. This tutoring program aims to help elementary school students master basic level English well. Based on the results of the situation analysis, the understanding and mastery of English at the elementary level of elementary school students in Pringgarata village is still low. This is not a strange thing because English is a foreign language so mastering it is not easy. Therefore, it is necessary to make efforts to grow and increase their awareness to learn outside class hours. This tutoring program also aims to foster student independence to study on their own at home. And with this effort, it is hoped that students will be able to improve their English skills and grades. This English learning guidance concerns the mastery of the four English skills, namely: listening (listening), reading (reading), speaking (speaking), and writing (writing). Besides, it is also taught about structure and vocabulary. The tutoring program that has been carried out has been successful. This can be seen from the enthusiasm of elementary school students to take part in this tutoring program. Their attendance reached 100%. And from the results of the learning evaluation, it appears that they have shown an increase in their English skills in all four skills, namely listening, reading, speaking and writing and two components of English, namely grammar and vocabulary.